Sensors and Advanced Sensing Techniques for Computer Vision Applications - Christos-Nikolaos Anagnostopoulos; Stelios Krinidis (Sensors)
Computer vision is a multidisciplinary field that enables machines to interpret and understand visual information from the world, simulating human vision [...]